Inhibition of BMP signaling overcomes acquired resistance to cetuximab in oral squamous cell carcinomas. (1st February 2018) - Yin, Jinlong; Jung, Ji-Eun; Choi, Sun Il; Kim, Sung Soo; Oh, Young Taek; Kim, Tae-Hoon; Choi, Eunji; Lee, Sun Joo; Kim, Hana; Kim, Eun Ok; Lee, Yu Sun; Chang, Hee Jin; et al.
Abstract: Despite expressing high levels of the epidermal growth factor receptor (EGFR), a majority of oral squamous cell carcinoma (OSCC) patients show limited response to cetuximab and ultimately develop drug resistance. However, mechanism underlying cetuximab resistance in OSCC is not clearly understood. Here, using a mouse orthotopic xenograft model of OSCC, we show that bone morphogenic protein-7-phosphorylated Smad-1, -5, -8 (BMP7-p-Smad1/5/8) signaling contributes to cetuximab resistance. Tumor cells isolated from the recurrent cetuximab-resistant xenograft models exhibited low EGFR expression but extremely high levels of p-Smad1/5/8. Treatment with the bone morphogenic protein receptor type 1 (BMPRI) inhibitor, DMH1 significantly reduced cetuximab-resistant OSCC tumor growth, and combined treatment of DMH1 and cetuximab remarkably reduced relapsed tumor growth in vivo . Importantly, p-Smad1/5/8 level was elevated in cetuximab-resistant patients and this correlated with poor prognosis. Collectively, our results indicate that the BMP7-p-Smad1/5/8 signaling is a key pathway to acquired cetuximab resistance, and demonstrate that combination therapy of cetuximab and a BMP signaling inhibitor as potentially a new therapeutic strategy for overcoming acquired resistance to cetuximab in OSCC. Highlights: BMP7-p-Smad1/5/8 signaling contributes to cetuximab resistance in OSCC. DMHI, a BMP signaling inhibitor, reduced cetuximab-resistant OSCC tumor growth. Combined treatment of DMH1 and cetuximab significantly reduced relapsed tumor growth in vivo. p-Smad1/5/8 overexpression in OSCC patients was associated with poor disease free survival.